Botoh sebagai Kekuatan Lokal dalam Suksesi Pilkades di Kabupaten Ponorogo - Try Cahyono; Jusuf Harsono; Khoirurrosyidin Khoirurrosyidin (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2018)
The practice of democracy in achieving through the village head election , apparently store various dynamics, Where much power local appear and indicated its existence, Botoh Is one of the ways is as a Local Strongment, Botoh Then offering an interesting choice in the form of money’s, To the community in order to support a candidate who support it, This in turn generated problems, because practices democracy that the requirements dnegan practices cheat.